On the Mechanical Properties of Popgraphene‐Based Nanotubes: a Reactive Molecular Dynamics Study. Issue 7 (9th March 2021) - Brandão, W. H. S.; Aguiar, A. L.; Ribeiro, L. A.; Galvão, D. S.; De Sousa, J. M.
Abstract: Carbon‐based tubular materials have sparked a great interest in future electronics and optoelectronics device applications. In this work, we computationally studied the mechanical properties of nanotubes generated from popgraphene (PopNTs). Popgraphene is a 2D carbon allotrope composed of 5‐8‐5 rings. We carried out fully atomistic reactive (ReaxFF) molecular dynamics for PopNTs of different chiralities ( n, 0 and 0, n ) and/or diameters and at different temperatures (from 300 up to 1200 K). Results showed that the tubes are thermally stable (at least up to 1200 K). All tubes presented stress/strain curves with a quasi‐linear behavior followed by an abrupt drop of stress values. Interestingly, armchair‐like PopNTs ( 0, n ) can stand a higher strain load before fracturing when contrasted to the zigzag‐like ones ( n, 0 ). Moreover, it was obtained that Young's modulus ( YMod ) (750–900 GPa) and ultimate strength ( σUS ) (120–150 GPa) values are similar to the ones reported for conventional armchair and zigzag carbon nanotubes. YMod values obtained for PopNTs are not significantly temperature‐dependent. While the σUS values for the 0, n showed a quasi‐linear dependence with the temperature, the n, 0 exhibited no clear trends. Abstract : Popgraphene Nanotubes : In this work we studied the elastic properties of Popgraphene nanotubes (PopNTs) composed of 5‐8‐5 carbon rings, via ReaxFF potential using molecular dynamics calculations. While we observed the independence of Young's modulus concerning the temperature for several chiralities, the elastic fracture quantities are close to the values found in the literature for conventional nanotubes, but they are strongly dependent of PopNTs chirality and also the temperature.